1971
DOI: 10.1021/j100677a013
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structure of L-alanyl-L-alanine

Abstract: L-Aktiiyl-L-alanine crystallizes in the tetragonal space group, 14, with a = 17.985 i : 0.005 and c = 5.154 rt 0.003 8. The crystal structure of this dipeptide was solved using noncentrosymmetric direct methods on 1396 reflections measured with Mo Ka! radiation on an automatic four-circle diffractometer; details of the phasing procedure are briefly discussed. Full-matrix least-squares refinement of' the structure yielded a conventional R = 0.866, with standard deviations of 0.005 8 and 0.3" in the bond lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 1 publication
2
34
0
Order By: Relevance
“…4, it is observed that for n r ¼ n p ¼ 5 kHz, the peak intensity of site F, along with sites A and B, decreases significantly as the RF field strength is increased. Site F is relatively remote from any 14 N spin (its strongest 13 C-14 N dipolar coupling is Àg C g N m_/(r CN 3 4p) ¼ À150 Hz, based on the reported crystal structure [24]) and one would hope not to see any effect from the decoupling sequence on the signal from this site. The decrease in signal intensity with increasing 14 N RF field strength suggests significant dipolar recoupling occurs, because the population transfer between 14 N spin states interferes with MAS averaging of the firstorder 13 C-14 N dipolar interaction in a similar manner to that used in TRAPDOR [25] and REAPDOR [26].…”
Section: Resultsmentioning
confidence: 99%
“…4, it is observed that for n r ¼ n p ¼ 5 kHz, the peak intensity of site F, along with sites A and B, decreases significantly as the RF field strength is increased. Site F is relatively remote from any 14 N spin (its strongest 13 C-14 N dipolar coupling is Àg C g N m_/(r CN 3 4p) ¼ À150 Hz, based on the reported crystal structure [24]) and one would hope not to see any effect from the decoupling sequence on the signal from this site. The decrease in signal intensity with increasing 14 N RF field strength suggests significant dipolar recoupling occurs, because the population transfer between 14 N spin states interferes with MAS averaging of the firstorder 13 C-14 N dipolar interaction in a similar manner to that used in TRAPDOR [25] and REAPDOR [26].…”
Section: Resultsmentioning
confidence: 99%
“…With the zwitterions and the anion at hand, interest was triggered for investigating the cation of II, in order to obtain the ®rst series of structures describing all three classical protonation states of a peptide. Crystal structures of two protonation states (as zwitterion and cation) were known for only nine peptides (all dipeptides), of which three were devoid of Gly residues [Ala-Ala (Fletterick et al, 1971) ± Ala-AlaÁHCl (Tomuka et al, 1969); Ala-PheÁ2-propanol (Go È rbitz, 1999) ± Ala-PheÁHClÁ2H 2 O (Cotrait & Barrans, 1974); Leu-Ala (Go È rbitz, 1997) ± Leu-Ala 1,5-naphthalenedisulfonate (Sudbeck et al, 1994)]. Surprisingly, the following experiments produced not only II as a regular cation in the nitrate salt (IIc), but also a structure in which a pair of peptide molecules have jointly taken up an H atom that serves to connect them by a strong ±COOÁ Á ÁHÁ Á ÁOOC± hydrogen bond, essentially a dimeric cation (IIdc).…”
Section: Introductionmentioning
confidence: 99%
“…The structures of all three peptides had been resolved previously. [6] The VI crystal packing has hexagonal symmetry with molecules forming helices with six dipeptides per turn. LS crystals have a unique crystal packing with the inner walls formed by leucine side chains and with right-handed helicity.…”
mentioning
confidence: 99%